Aproximación al sistema de lugares centrales de la provincia de León - Cortizo Álvarez, José (Estudios humanísticos. Geografía, historia y arte, 1988)
In this paper, we intend to confirm that the organization of territory in the province of Leon is made by means of a polarized hierarchical structure of the market places. In order to achieve our purpose, we analyze the population as perceivers of a rent and as the basis for demand; we also deal with commercial activities and service industries, for they are closely related to the distribution of the central-places theory, we attempt to establish the hierarchy of these activities as the basis for the functional hierarchization of market places and their areas of influence.